(untitled) (Journal of Hama University, 2022)
This study aimed to evaluate the expectations of orthodontic treatment for adult patients with class II div 1 malocclusion in a Syrian sample. Fifty patients with class II div 1 malocclusion were enrolled in this cross-sectional study. A questionnaire for assessment orthodontic patients expectations that developed by Sayers and Newton was used in this study. The questionnaire included 14 questions about the problems, pain, limitations, social impact, treatment times and finally treatment outcomes using fixed orthodontic appliances. The differences between males’ and females’ expectations as well as the method error of using this questionnaire were also tested.Problems (like pain, troubles during eating, food and drinks type restriction) were slightly to moderately expected to occur by the most of the patients. On the other hand, just a small part of them had a high expectations for this problems occurrence. Most of the patients also expected a positive social impact of fixed orthodontic appliance placement. More than one year and 2-4 weeks were the most expected about the period of orthodontic treatment and checkup intervals respectively. The majority of the patients highly expected a positive treatment outcomes. The differences between males’ and females’ expectations were not significant (P>0.05). The assessment of method error showed a high inter-class correlation coefficient between test-retest measures (ICC>0.88) without any significant differences (P>0.05). The majority of Syrian patients expectations were realistic about this type of treatment for class II div 1 malocclusion patients.